1988
DOI: 10.1002/app.1988.070350115
|View full text |Cite
|
Sign up to set email alerts
|

Influence of molecular weight distribution on the linear viscoelastic properties of polymer blends

Abstract: SynopsisLiterature data for the dynamic viscoelastic properties of binary blends of nearly monodisperse polybutadienes, polystyrenes, and poly(methy1 methacry1ate)s was analyzed using logarithmic plots of dynamic storage modulus G' versus loss modulus G", based on a recent theoretical study by Han and Jhon.% It has been found that for binary blends of monodisperse polymers with molecular weights M much greater than the entanglement molecular weight Me, the value of G' in log G'-log G" plots becomes independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 49 publications
(35 reference statements)
4
40
0
Order By: Relevance
“…In other words, the two normal stress differences of ( 11 Ϫ 22 ) and ( 11 Ϫ 33 ) were almost identical, and the normal stress difference ( 11 Ϫ 33 ) was proportional to the square root of 12 . Thus, their results were consistent with a linear viscoelastic theory such as the Maxwell model in which the plot of ( 11 Ϫ 33 ) versus 12 gives rise to the slope of factor 2 in log-log scale as the Cole-Cole plot of GЈ vs GЉ (44,45). Consequently, ͗n 11 Ϫ n 33 ͘ is proportional to the square root of 12 and n 12 ϰ ͌ |͗n 11 Ϫ n 33 ͘| for a linear viscoelastic material.…”
Section: Correlation Of the Stress Optical Rulesupporting
confidence: 77%
“…In other words, the two normal stress differences of ( 11 Ϫ 22 ) and ( 11 Ϫ 33 ) were almost identical, and the normal stress difference ( 11 Ϫ 33 ) was proportional to the square root of 12 . Thus, their results were consistent with a linear viscoelastic theory such as the Maxwell model in which the plot of ( 11 Ϫ 33 ) versus 12 gives rise to the slope of factor 2 in log-log scale as the Cole-Cole plot of GЈ vs GЉ (44,45). Consequently, ͗n 11 Ϫ n 33 ͘ is proportional to the square root of 12 and n 12 ϰ ͌ |͗n 11 Ϫ n 33 ͘| for a linear viscoelastic material.…”
Section: Correlation Of the Stress Optical Rulesupporting
confidence: 77%
“…All the data measured at various temperatures and molecular weights can be described by a single master curve in the log(G 0 ) versus log(G 00 ) plot. [23] Experimental investigations have also shown that the SCB would not affect the master curve. However, any change in chain topology, such as LCBing, and PDI would lead to a significant deviation of data points from the master curve.…”
Section: Time-temperature Superposition and Flow Activation Energymentioning
confidence: 99%
“…However, any change in chain topology, such as LCBing, and PDI would lead to a significant deviation of data points from the master curve. [4b] In the terminal region, theoretical derivations [23] have shown that, for monodisperse linear polymers with M > M e ,…”
Section: Time-temperature Superposition and Flow Activation Energymentioning
confidence: 99%
“…G′(ω) at high frequencies reduced with BE fraction, since highly deformed BE particles acted as a role of plasticizer. Moreover, the relationship between the storage modulus (G′) and the loss modulus (G″) (Han plot) can be used to characterize the miscibility of polymer blends [51,52]. The Han plot of PLA/BE blends is displayed in Fig.…”
Section: Rheological Propertiesmentioning
confidence: 99%